2004
DOI: 10.1111/j.1601-5223.1993.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Flavonoid Biosynthesis in Barley

Abstract: Mutations in genes associated with the pathway of flavonoid biosynthesis can readily be induced in barley and since 1977 more than 700 mutants have been isolated in which the biosynthesis of anthocyanin and/or proanthocyanidin is affected. Diallelic crosses have localized a majority of the mutants to 28 different complementation groups (Ant genes). Mutations in ten of the Ant genes result in a blocked synthesis of proanthocyanidins in the testa layer of the grains, whereas mutations in 18 Ant gene loci only af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 67 publications
2
58
0
3
Order By: Relevance
“…Because these compounds remain colorless until oxidative browning occurs during seed maturation, we used a colorimetric test to determine their presence during early seed development (Jende-Strid, 1993). In wild-type seed coats, uncolored PAs and their precursors were detected by their dark red staining with vanillin in the endothelium covering the whole seed body, hereafter called the endothelium body, as well as in the endothelial cells around the chalazal bulb and the micropylar area ( Figure 2D).…”
Section: Pigmentation Pattern In Tt16 Seedsmentioning
confidence: 99%
“…Because these compounds remain colorless until oxidative browning occurs during seed maturation, we used a colorimetric test to determine their presence during early seed development (Jende-Strid, 1993). In wild-type seed coats, uncolored PAs and their precursors were detected by their dark red staining with vanillin in the endothelium covering the whole seed body, hereafter called the endothelium body, as well as in the endothelial cells around the chalazal bulb and the micropylar area ( Figure 2D).…”
Section: Pigmentation Pattern In Tt16 Seedsmentioning
confidence: 99%
“…The barley (Hordeum vulgare) lines Ca33787 (wild type) and the ant310 mutant (Jende-Strid, 1993;Reuber et al, 1997;Druka et al, 2003) while plants used for protoplast, miniprotoplast, and vacuole isolations performed in Zurich were grown with a photoperiod of 14 h. In both locations, phytotrons were set to 20°C and a relative humidity of 60% to 70%.…”
Section: Plant Materials and Growth Conditionmentioning
confidence: 99%
“…Over 600 such ant mutants have been described. These mutants define 10 loci: three loci defined by ant17, ant18 and ant30 encode F3H, DFR and CHI,respectively;and six loci (ant19,ant25,ant26,ant27,ant28 and ant29) are defective in conversion of leucoanthocyanidin to proanthocyanidins ( Jende-Strid, 1991) ( Jende-Strid, 1993). More detailed phenotypic and molecular analysis has indicated that the tenth locus, Ant13, is a regulatory gene for the general flavonoid pathway.…”
Section: Transcription Factors Controlling the Biosynthesis Of Proantmentioning
confidence: 99%